Penerapan Dasar Teknik Elektro di Fast Robotic Bantul Yogyakarta - Johanes Rendy Lamoren; Rahmat Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
The significance of learning the fundamentals of electrical engineering in the present period, as doing so ensures that we will have access to a wide range of rewarding employment opportunities. Fast Robotic is a company that offers training for building assembled robots as well as selling robots. Fast Robotic sells a variety of robots and their replacement parts, so in this article I'll demonstrate how crucial having a foundational understanding of electronics engineering is in order to produce different robot assemblies and create a company like Fast Robotic. Using an example of the application Fast Robotic's basic electrical engineering enables us to understand the significance of having a foundational understanding of electrical engineering.